How to Write Abstracts for Health Research Articles ? - Joel Rey U. Acob (Health Notions, 2017)
Abstract writing is very important, because good abstract is one of the determining factors for the passing of an article submission to scientific journals, proceedings, and other publication media. In this journal (Health Notions) it is also explicitly communicated in the menu of "Author guidelines" that specifically for research articles, abstracts must be included(1). Abstracts of a health research article seem simple, but it is often found that the abstracts written turned out to not be able to represent the contents of the paper as a whole. Abstracts from a health research article seem simple, but it is often found that the abstracts written turned out to not be able to represent the contents of the paper as a whole. Therefore, tips on abstract writing are important, especially for beginner writers.